A quarter of patients time their early rheumatoid arthritis onset differently than physicians. Issue 2 (14th November 2019) - Ellingwood, Leah; Kudaeva, Fatima; Schieir, Orit; Bartlett, Susan J; Bessette, Louis; Boire, Gilles; Hazlewood, Glen S; Hitchon, Carol; Keystone, Edward; Tin, Diane; Thorne, Carter; Bykerk, Vivian P; et al.
Abstract : Objective: Early rheumatoid arthritis (RA) treatment requires timely recognition. This large, multicentre study compared patient-reported vs physician-reported onset of early RA. Methods: Patients from the Canadian Early ArThritis CoHort with early/suspected RA (persistent synovitis <1 year) completed questionnaires asking about the date of symptom onset; and rheumatologists date of onset for persistent synovitis. Groups with similar reported timing (patient and physician) versus differing timing of 30 days or more were compared. Results: In 2683 patients, the median patient symptom duration (IQR) was 178 days (163) and physician-reported duration was 166 (138). 1940 (72%) patients had similar patient-reported and physician-reported onset (<30 days), whereas 497 (18%) reported onset 30 or more days preceding physicians, and 246 (9%) 30 or more days after physicians. Patients reporting onset preceding physicians had lower baseline Disease Activity Score based on 28 joint count, swollen joint counts and erythrocyte sedimentation rate (p<0.05). Patients reporting onset after physicians were more likely to be rheumatoid factor positive (p<0.001) and had higher anticitrullinated protein antibody titres (p<0.009). Regression showed low income, smoking, fibromyalgia, osteoarthritis and baseline non-methotrexate non-biological disease-modifying antirheumatic drug use were predictors for longer patient-reported symptoms. At 12 months, patients reporting longer symptom duration than physicians had lower rates of Simplified Disease Activity Index remission and higher physician global assessments. Conclusion: Over one-fourth of patients reported differences of >1 month in symptom onset from their rheumatologist. Patients with longer symptom durations had less improvement at 1 year, which may be reflective of comorbid musculoskeletal conditions.